Про роботу НАН України в період воєнного стану (стенограма доповіді на засіданні Президії НАН України 23 серпня 2024 р.) - Горбулін, В.П. (Вісник НАН України, 2024)
У доповіді розглянуто особливості діяльності Національної академії наук України в період дії воєнного стану, наведено деякі результати виконання Цільової науково-технічної програми оборонних досліджень НАН України та інші розробки академічних установ, спрямовані на зміцнення обороноздатності та безпеки держави, розвиток військової та цивільної медицини тощо. Окрему увагу приділено внеску вчених-соціогуманітаріїв у підвищення національної стійкості країни, протидію гібридним та інформаційним загрозам, відновлення економіки в післявоєнний період. The report discusses the peculiarities of the work of the National Academy of Sciences of Ukraine during the period of martial law, presents some results of the implementation of the Targeted Scientific and Technical Program of Defense Research of the National Academy of Sciences of Ukraine and other developments of academic institutions aimed at strengthening the defense and security of the state, development of military and civilian medicine, etc. Particular attention is paid to the contribution of social scientists and humanities scholars to enhancing the country’s national resilience, countering hybrid and information threats, and economic recovery in the postwar period.